Efficacy and Safety of Remimazolam for Procedural Sedation: A Meta-Analysis of Randomized Controlled Trials With Trial Sequential Analysis - Jhuang, Bo-Jyun; Yeh, Bo-Han; Huang, Yen-Ta; Lai, Pei-Chun (Frontiers in Medicine, 2021)
Background: Remimazolam is a new ultrashort-acting benzodiazepine. Remimazolam has been approved for procedural sedation by the US Food and Drug Administration in 2020. However, prior trials and the participants they enrolled were limited. Aim: In this meta-analysis, we investigated the effectiveness and adverse events (AEs) of remimazolam during procedural sedation. Materials and Methods: The study protocol was registered (doi: 10.37766/inplasy2020.8.0043), and six databases were searched. We performed meta-analysis, trial sequential analysis (TSA), and Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) methodology for judging the certainty of evidence (CoE). Results: A total of five randomized controlled trials with 1,248 participants were included. Compared with the use of midazolam, the utilization of remimazolam resulted in an increase in procedure success rate [odds ratio (OR) = 9.01, 95% confidence interval (CI): 2.35–34.57], a reduction in the application of rescue medication (OR = 13.58, 95% CI: 3.46–53.28), a decrease in time to recovery [minutes, weighted mean difference (WMD) = −5.70, 95% CI: −8.68 to −2.72], and a better cognitive recovery of Hopkins Verbal Learning Test-Revised (WMD = 5.22, 95% CI: 2.88–7.55). No difference was found in completion of procedure (OR = 1.68, 95% CI: 0.72–3.90) with inconclusive in TSA. Despite no difference of total AEs (OR = 0.60, 95% CI: 0.24–1.50), more detailed analysis of AEs remained inconclusive in TSA. The GRADE assessment demonstrated low to very low CoE. Conclusion: Our analysis suggested that remimazolam may be a better choice for procedural sedation than midazolam. Nevertheless, further studies are warranted to conclusively establish its safety.